European Dialogue : The Third Biennale of Sydney : at The Art Gallery of New South Wales. - The Third Biennale of Sydney, 1979 (Sydney : The art gallery of New South Wales, 1979)
Abramovic, Mariana & Ulay ; Arman ; Beuys, Joseph ; Boltanski, Christian ; Broodthaers ; Panamarenko ; Alechinsky, Pierre ; Girke, Raimund ; Hockney, David ; Hofkunst, Alfred ; Lassnig, Maria ; Owen, Robert ; Paolini, Giulio ; Parr, Mike ; Penck, A.R. ; Rosenbach, Ulrike ; Spoerri, Daniel ; Tinguely, Jean ; Van Elk, Ger ; Raysse, Martial ; Schoonhoven, Jan J. ; Starczewski, Antoni ; Thomkins, André ; Visser, Carel ; etc.
The Third Biennale of Sydney at The Art Gallery of New South Wales, The Australian Centre for Photography and other venues, 14 April - 27 May 1979
English
kunstcatalogus
Keywords: Europa